A comparison of physical function, nutritional habits and neurocognitive constructs between urban and rural Costa Rican older adults - Serrano Moreno, Walter (2019)
Purpose: To compare nutritional habits, physical function and psychological constructs between Costa Rican older adults from urban and rural zones. Methods: Male and female older adults aged ≥ 65 yr. from urban (n = 185) and rural (n = 109) Costa Rica were assessed on nutritional habits, physical function measures, and cognitive function by a face-to-face interview. Results: Rural older adults consumed more daily carbohydrates, protein, and energy at breakfast and lunch (p < 0.05 for all), and more carbohydrates (p ≤ 0.001), fat (p = 0.002), protein (p ≤ 0.001), and energy (p ≤ 0.001) at dinner than urban elderly. Aerobic power (p = 0.044) was higher in urban compared to rural elderly. A correlation was found between aerobic power and global fatigue (r = -0.20, p = 0.014) in urban elderly. Lifetime cognitive activity correlated to total energy (r = 0.37, p = 0.003), carbohydrate (r = 0.37, p = 0.002), and protein (r = 0.34, p = 0.005) consumption in rural elderly. Higher depression scores (p = 0.048), and lower lifetime cognitive activity were observed in urban compared to rural elderly (p = 0.004). Conclusion: The health profile is positive for either group depending on the variable analyzed, except for a higher aerobic power, which provides benefits to the entire cohort.